A Sterically Encumbered 13/15 Cycle and its Cleavage with N‐heterocyclic Carbenes and other Lewis Bases. Issue 22 (12th September 2016) - Kapitein, Manuel; Balmer, Markus; von Hänisch, Carsten
Abstract : Herein, the latest results on the topic of NHC‐stabilized, monomeric group 13 metalsilylphosphanides, with the focus on the sterically demanding [Ga t Bu2 Rx ]‐fragment ( x = 1, 2) are presented. The synthesis and characteristics of the cyclic compound [ t Bu2 GaP(H)Si t BuPh2 ]2 (1 ), followed by the cleavage of this cycle with different Lewis bases like pyridine, DMAP or the I i Pr carbene is described for the first time. The compounds [(LB) t Bu2 GaP(H)Si t BuPh2 ] [LB = pyridine (2 ) and LB = DMAP (3 )] are investigated as possible precursors for ligand exchange reactions with sterically demanding NHCs like IMes or IDipp, since the latter show no reaction with the four‐membered cycle1 due to their high steric strain. The pros and cons of an alternative pathway for the synthesis of monomeric complexes by means of salt elimination are pointed out. Abstract :